The information content of non-current assets / Zaleha Abdul Shukor - Abdul Shukor, Zaleha (2007)
This thesis study examines the information content of non-current assets (NCA) during economic crisis period. Specifically this study asked two questions. First, whether NCA information content still exist during economic crisis period. Abandonment option hypothesis suggest firms’ net book value of equity has more information content than earnings, conceptually during economic crisis period. However there is vague evidence in prior literature with regards to NCA information content during economic crisis period even though NCA is the major component of net book value of equity. Second, this study asked whether NCA information content during economic crisis period might be diluted due to NCA having two major components of opposite nature, tangible and intangible NCA. There is very little evidence on the information content of tangible together with intangible NCA during economic crisis period in prior literature. This thesis research empirically test information content of NCA based on multiple regressions of three decision making models. The models are the analysts’ earnings forecasts accuracy model, the price model and the returns model. Sample data consist of all firms listed on the main board of Bursa Malaysia throughout years 1990 until 2001, inclusive. Sample data is partition into three main sub-samples of three different economic conditions, namely pre-crisis, crisis and post-crisis periods. Focus of thesis study is on crisis period proxy by the Asian financial crisis being years 1997 and 1998. Pre-crisis period cover years before 1997 and post-crisis period cover years after 1998. Pre-crisis period results suggest NCA have less information content compared to post-crisis period results. Economic crisis period results suggest NCA have information content based on NCA association with dependent variables in all three main models. Results also suggest NCA information content is better for decision on firms’ value than for predicting firms’ performance. Price models consistently show higher explanatory power compared to accuracy and returns models. In further analysis on crisis period, results provide evidence NCA information content might be diluted when examined as one item compared to when examined as components of tangible and intangibles. Findings imply that abandonment option hypothesis could be refined by investigating NCA as components rather than as one item. Findings provide evidence to financial statement preparers and accounting regulators that NCA is important information for decision making by capital market participants during economic crisis period.